Deux versions du modèle dans le Timée - Pitteloud, Luca Jean (Journal of Ancient Philosophy, 2015)
The purpose of this article is to emphasize two alternatives introduced by Plato in the Timaeus in order to describe the model. In her argumentation developed in Nature and Divinity in Plato's Timaeus, S. Broadie affirms that a metaphysical reading of the Timaeus should be rejected in favor of a cosmological interpretation. To justify this idea, Broadie distinguishes between two ways of understanding what could be the model at which the demiurge looks in order to shape the cosmos, namely an original or a plan. According to Broadie, since it is the second alternative that is present in the Timaeus, and since this alternative is closely related to a cosmological interpretation of the dialogue, then it would be a mistake to offer a metaphysical reading of Timaeus’ discourse. However, as we shall see, the Timaeus associates the model not only with a plan but also with an original, which suggests that the cosmological reading of this dialogue should be connected with a metaphysical interpretation. Far from leading to a contradiction, the fact that Plato offers two versions of the model could mean that the question of the nature of Forms is not completely absent from the dialogue. In providing a double description of the model, and in offering metaphysical considerations within his cosmological discourse, Plato seems to provide an account of the nature of the intelligible and its explanatory role with regards to an understanding of what is the universe in all its complexity, for the two versions will allow to justify 1) the nature of cosmos as the best possible realization and 2) the ontological status of the sensible which possesses its own degree of being. Are these two versions fully compatible? We will suggest in our conclusion that the tension induced by their presence in the same dialogue actually allows a better understanding of Timaeus’ speech.